Deployment and uptake of COVID-19 vaccines for refugees and migrants in Ecuador - Martens, Cheryl; Milan, Taymi; Mena Ayala, María Belén; Teran, Enrique; Benavente, Pierina; Tran, N. T.; Blanchet, Karl (Frontiers in Public Health, 2025)
This study examines access and uptake of COVID-19 vaccines among refugees and migrants in Ecuador, including those with regular and irregular migration status. Conducted in Quito, Manta, and Huaquillas with 344 participants, the article reports on the survey data to assess vaccination access, barriers, and enablers. Findings show that 94% of respondents received at least one vaccine dose, despite 69% having irregular status. However, gaps remained in second and booster dose uptake, which was linked to misinformation and administrative barriers such as lack of documentation, discrimination and stigma, especially from healthcare and security personnel at vaccine sites. Key facilitators included receiving support from non-governmental organizations, mobile health brigades, and pressure from international organizations. The study concludes that although Ecuador made vaccines accessible to migrants, systemic challenges, such as data gaps, xenophobia, and insufficient outreach, hindered equitable coverage and limited the rights of migrants and refugees. Improved communication, flexibility in relation to documentation are recommended to ensure equitable access vaccines.